EUTHANASIA: THE RIGHT TO DIE - Tonél, Rodrigo; Sturza, Janaína Machado; Dilkin, Rogério De Almeida; Berwig, Aldemir; Gagliardi, André (Salão do Conhecimento, 2017)
Interdisciplinary theme among the areas of education, law and social communication.